2021
DOI: 10.1007/s43032-020-00449-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mitochondrial Genetic Variants in ND1, ND2, ND5, and ND6 Genes on Sperm Motility and Intracytoplasmic Sperm Injection (ICSI) Outcomes

Abstract: Sperm mitochondrial dysfunction causes the generation of an insufficient amount of energy needed for sperm motility. This will affect sperm fertilization capacity, and thus, most asthenozoospermic men usually require assisted reproductive techniques. The etiology of asthenozoospermia remains largely unknown. The current study aimed to investigate the effect of mitochondrial genetic variants on sperm motility and intracytoplasmic sperm injection (ICSI) outcomes. A total of 150 couples from the ICSI cycle were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Besides, two studies were conducted in our laboratory, the first study demonstrated that the frequencies of total mitochondrial variants in four mitochondrial genes (nicotinamide adenine dinucleotide hydrogen (NADH) dehydrogenase 1 (ND1), NADH dehydrogenase 2 (ND2), NADH dehydrogenase 5 (ND5), and NADH dehydrogenase 6 (ND6)) were negatively correlated with the percentages of sperm motility and ICSI outcomes, namely 13708 G>A, 4216T>C and 12506T>A [5,33]. Mughal et al discovered that mtDNA mutations had a major impact on sperm production, resulting in infertility, by influencing various sperm motility parameters [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, two studies were conducted in our laboratory, the first study demonstrated that the frequencies of total mitochondrial variants in four mitochondrial genes (nicotinamide adenine dinucleotide hydrogen (NADH) dehydrogenase 1 (ND1), NADH dehydrogenase 2 (ND2), NADH dehydrogenase 5 (ND5), and NADH dehydrogenase 6 (ND6)) were negatively correlated with the percentages of sperm motility and ICSI outcomes, namely 13708 G>A, 4216T>C and 12506T>A [5,33]. Mughal et al discovered that mtDNA mutations had a major impact on sperm production, resulting in infertility, by influencing various sperm motility parameters [34].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial mutations are very common etiological pathogenic factors in energy-demanding organs such as muscles and the nervous system and are related to musculoskeletal and neurodegenerative disorders [ 4 ]. In addition, genetic alteration in the mtDNA may have significant effects on normal spermatogenesis and subsequently on fertilization [ 5 , 6 ]. Several reports have shown that mitochondrial dysfunction could lead to complete or partial spermatogenesis arrest and be an important causative factor in male infertility [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A proposed solution for such infertility is ICSI. Studies now show that although mitochondrial DNA variation has a negative impact on ICSI outcomes, it is still possible (Al Smadi et al 2021). Sperm DNA integrity is one of the vital prognostic factors of male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with varicocele, alcoholic problems and cigarette smokers and patients with age above 40 were excluded from this study. Semen collection, sperm preparation for ICSI, oocyte denudation, the (ICSI) technique, fertilisation assessment, embryo grading, embryo cleavage score and embryo quality score were described previously (Al Smadi et al., 2021). This study was approved by the Jordanian Royal Medical Services‐Human Research Ethics Committee on 30/7/2018 (TF3/1/Ethics Committee/9,126).…”
Section: Methodsmentioning
confidence: 99%